O processo decisorio de criação do Centro Cultural Banco do Brasil - Lemos, Ana Heloísa da Costa (1994)
As the decision making process plays the mam role in the organizations' management it has been the target of the analysis of the administration theoreticians, in interpretations that emphasize either the rational, the organizational, the polítical and , recently, the intuitive aspects. However, the difterent models don't assure the complete understanding about the decisory phenomenon as each one favours certain aspects of the analysis, leaving others that are as important or more than that one focused on. For this reason an analysis, of an specific decision process has been initiated : the creation of the Centro Cultural Banco do Brasil (CCBB). Through this analysis, it has been possible to reinforce the believc that as long as complcx or unstructurcd decisions are concerned, there isn't only a single explicative factor but intermingled elements from diferent origins